2016
DOI: 10.1111/cdev.12484
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of the Glucocorticoid Receptor Gene Promoter in Preschoolers: Links With Internalizing Behavior Problems

Abstract: Accumulating evidence suggests that early adversity is linked to methylation of the glucocorticoid receptor gene NR3C1, which is a key regulator of the hypothalamic-pituitary-adrenal (HPA) axis. Yet no prior work has considered the contribution of methylation of NR3C1 to emerging behavior problems and psychopathology in childhood. The current study examined links between methylation of NR3C1 and behavior problems in preschoolers. Data were drawn from a sample of preschoolers with early adversity (n=171). Child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
93
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(108 citation statements)
references
References 56 publications
11
93
1
3
Order By: Relevance
“…This research is in its infancy and is just beginning to integrate epigenetic processes into more complete models of adversity, the HPA axis, and psychopathology. One exception, as noted previously, found methylation of the GR gene mediated between maltreatment and internalizing problems (Parade et al., ). This investigation, however, did not include direct assessments of cortisol or gene expression which are needed.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…This research is in its infancy and is just beginning to integrate epigenetic processes into more complete models of adversity, the HPA axis, and psychopathology. One exception, as noted previously, found methylation of the GR gene mediated between maltreatment and internalizing problems (Parade et al., ). This investigation, however, did not include direct assessments of cortisol or gene expression which are needed.…”
Section: Discussionmentioning
confidence: 52%
“…Longer time in orphanage care was associated with lower methylation of the FKBP5 gene during adolescence (Non et al., ), something that might put youth at risk for PTSD. Finally, increased NR3C1 methylation mediated between maltreatment during the past 6 months and concurrent internalizing behaviors in preschoolers (Parade et al., ). Thus, epigenetic pathways may mediate between early adverse care and socioemotional outcomes.…”
Section: Sensitive Periods For Programming the Hpa Axismentioning
confidence: 99%
“…In a cross‐sectional analysis of high‐risk preschoolers, Parade et al. () found that higher DNAm levels at exons 1D and 1F (extracted from saliva) associated with higher internalising – but not externalising – behaviour problems. Consistent with this, Dadds, Moul, Hawes, Mendoza Diaz, and Brennan () reported that increased DNAm in the 1F region across whole blood and saliva associated with morning cortisol levels and higher risk of co‐occurring internalising problems among clinically referred conduct disordered children.…”
Section: Dnam and Child Psychopathology: The B Pathmentioning
confidence: 99%
“…Specifically, using a sample of preschoolers, approximately half of which have documented maltreatment within 6 months of the baseline assessment, we examined the effect of maltreatment and other environmental adversity on short-term change in methylation to begin to characterize within-child epigenetic changes during this sensitive developmental period. We assessed DNA methylation of the well characterized exon 1 F , and extended this research to exon 1 D which also has support from cross-sectional studies for a role in these processes (Hompes et al, 2013; Parade et al, 2016; van der Knaap et al, 2014; Weder et al, 2014). …”
mentioning
confidence: 94%